The formation of the Soviet Union : communism and nationalism 1917-1923 - Pipes, Richard; Harvard University. Russian Research Center (London : Harvard University Press, 1997)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: politieke geschiedenis; Sovjet-Unie.